EVALUASI KUALITAS DESAIN PEMBELAJARAN EKONOMI DI SEKOLAH MENENGAH ATAS MENGGUNAKAN MODEL COUNTENENCE STAKE - Ikbal Barlian; Dewi Koryati; Riswan Jaenudin (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2020)
The purpose of this study is to evaluate the quality of economics teacher learning design.The evaluation method uses the Stake Countenance Model.Data were collected through observation, interviews, and documentation obtained from 2 economics teachers as evaluants who teach in social studies class X at different high schools.The data analysis technique used is descriptive qualitative.The conclusion of the research is;1) the average value of the lesson plan matching of the two economics teachers was 83.33% (Good);2) Good categorized learning (transaction) (78.26%);and 3) learning outcomes have reached KKM, with an actuality of 82%.However, economics teachers are advised to improve the quality of the process and assessment of learning outcomes by training students to improve higher-order thinking skills.